Sporadic pregnancy loss and recurrent miscarriage. (November 2020) - Devall, Adam J.; Coomarasamy, Arri
Abstract: Progesterone is essential for the maintenance of pregnancy, and progesterone deficiency is associated with miscarriage. The subject of whether progesterone supplementation in early pregnancy can prevent miscarriage has been a long-standing research question and has been investigated and debated in the medical literature for over 70 years. During this time, several different progestogens have been synthesised and tested for the prevention of miscarriage. In this chapter, we describe the prior evidence alongside the latest research using micronized natural progesterone as well as synthetic progestogens, which were used to treat both recurrent and threatened miscarriage. The totality of evidence indicates that women with a past history of miscarriage who present with bleeding in early pregnancy may benefit from the use of vaginal micronized progesterone. The clinical implications of the findings are discussed. Highlights: Two important clinical risk factors for miscarriage are a history of previous miscarriages and vaginal bleeding. The risk of miscarriage increases with the number of previous miscarriages a woman has suffered. Vaginal micronized progesterone treatment started at the time of presentation with vaginal bleeding and continued to 16 completed weeks of gestation is able to prevent miscarriage in women with a history of one or more previous miscarriages.